Pemberian Infusa Kulit Buah Naga Merah (Hylocereus polyrhizus) terhadap Produktivitas Ayam Broiler - Zairiful, Z; Marya, D T; Lustanti, R D (Politeknik Negeri Lampung, 2024)
Broiler chicken is a type of livestock that has a short maintenance time ranging from 28-35 days this causes many farmers to cultivate broiler. Broiler chickens have high stress level that can interfere with broiler productivity, therefore it is necessary to minimize stress levels in broilers by providing antioxidants that can inhibit the oxidation process in livestock. Red dragon fruit peel contains antioxidant such as flavonoid, terpenoid, vitamin C, saponin and tannin which are sources of natural antioxidant. This study aims to analyze the benefit of red dragon fruit peel on broiler productivity. The material used is 100 DOC and red dragon fruit peel which is processed into infusion. Analysis of the data used in this study is statistical analysis paired until T-test with a confidence level of 5% and two treatments P0 as a control and P1 administration of red dragon fruit peel infusion at a level of 12%. The variables observed in the study were ration consumption, body weight gain, conversion ration, mortality and income over feed cost. The result showed that there was a significant difference in the productivity of broiler chicken for giving red dragon fruit peel infusion at a level of 12%.